Prognostication and optimal criteria of circumferential margin involvement for esophageal cancer after chemoradiation and esophagectomy - Potdar, Ankit; Chen, Ke-Cheng; Kuo, Shuenn-Wen; Lin, Mong-Wei; Liao, Hsien-Chi; Huang, Pei-Ming; Lee, Yi-Hsuan; Wang, Hsiu-Po; Han, Ming-Lun; Cheng, Chia-Hsien; Hsu, Chih-Hung; Huang, Ta-Chen; et al. (Frontiers in Oncology, 2023)
Purpose Circumferential radial margin (CRM) involvement by tumor after resection for esophageal cancer has been suggested as a significant prognostic factor. However, the prognostic value of CRM involvement after surgery with neoadjuvant concurrent chemoradiotherapy (CCRT) is unclear. This study aimed to evaluate the prognostic value of and survival outcomes in CRM involvement as defined by the Royal College of Pathologists (RCP) and the College of American Pathologists (CAP) for patients with esophageal cancer undergoing neoadjuvant CCRT and esophagectomy. Methods A total of 299 patients with esophageal cancer who underwent neoadjuvant CCRT followed by esophagectomy between 2006 and 2016 were enrolled in our study. The CRM status of the specimens obtained was determined pathologically according to both the CAP and RCP criteria. Survival analyses were performed and compared according to the two criteria. Results Positive CRM was found in 102 (34.1%) and 40 (13.3%) patients according to RCP and CAP criteria, respectively. The overall and progression-free survival rates were significantly lower in the CRM-positive group than in the CRM-negative group according to both the RCP and CAP criteria. However, under multivariate analysis, in addition to pathological T and N staging of the tumor, only CAP-defined CRM positivity was a significant prognostic factor with adjusted hazard ratios of 2.64 (1.56-4.46) and 2.25 (1.34-3.78) for overall and progression-free survival, respectively (P < 0.001). Conclusion In patients with esophageal cancer undergoing neoadjuvant CRT followed by esophagectomy, CAP-defined CRM positivity is an independent predictor of survival. Adjuvant therapy should be offered to patients with positive CRM.